2013
DOI: 10.1186/1556-276x-8-170
|View full text |Cite
|
Sign up to set email alerts
|

Biomimetic one-pot synthesis of gold nanoclusters/nanoparticles for targeted tumor cellular dual-modality imaging

Abstract: Biomimetic synthesis has become a promising green pathway to prepare nanomaterials. In this study, bovine serum albumin (BSA)-conjugated gold nanoclusters/nanoparticles were successfully synthesized in water at room temperature by a protein-directed, solution-phase, green synthetic method. The synthesized BSA-Au nanocomplexes have fluorescence emission (588 nm) of gold nanoclusters and surface plasmon resonance of gold nanoparticles. The BSA-Au nanocomplexes display non-cytotoxicity and excellent biocompatibil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
36
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(38 citation statements)
references
References 35 publications
1
36
1
Order By: Relevance
“…These findings suggested that Au-BSA-DOX-FA nanocomposites also simultaneously offer targeting therapy with less histotoxicity, owing to FA-mediated endocytosis and the intracellular release of DOX as a consequence. 47 …”
Section: CMmentioning
confidence: 99%
“…These findings suggested that Au-BSA-DOX-FA nanocomposites also simultaneously offer targeting therapy with less histotoxicity, owing to FA-mediated endocytosis and the intracellular release of DOX as a consequence. 47 …”
Section: CMmentioning
confidence: 99%
“…[53] regarding the toxicity of gold NPs both in vitro and in vivo [105]. Gold NPs have successfully been used for several biomedical approaches such as photo-thermal therapy [106,107], cancer diagnosis [108], tumor imaging [109,110], and drug delivery [111,108]. The plasmon resonance features of gold NPs enable their detection in biological systems [112].…”
Section: Doxorubicinmentioning
confidence: 99%
“…Another group used BSA-conjugated gold NPs, which was surface modified by FA. They showed that while the BSAgold NPs had no effects on the MGC803 gastric cancer cells, FA-modified NPs could selectively target them [110]. Similarly, FA-conjugated 6-mercaptopurine (6MP)-loaded gold NPs could potently kill FR-expressing HeLa and KB cells both in vitro and in vivo [119].…”
Section: Doxorubicinmentioning
confidence: 99%
See 1 more Smart Citation
“…CD spectra show that there is loss of secondary structure of enzyme during synthesis of silver NPs[50]. The secondary structural analysis reveals that native cellulase contains 85.61% of α-helix which is completely lost during the synthesis of silver NPs and there is formation of β-sheet (44.79%).…”
mentioning
confidence: 99%